2015
DOI: 10.1016/j.econmod.2014.10.023
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of systemic stress and interdependencies within the Eurozone and Euro Area countries

Abstract: One of the most challenging issues that economists are dealing with is the investigation of the financial turmoil in Eurozone economies. Particularly, the issue of exposing the potential crisis transmission channels has attracted considerable interest.Aiming to contribute to this literature, we construct financial stress indices on a country level and explore further the potential inter-reactions between the source causes of systemic risk. The country specific index consists of a wide number of series drawn fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In particular, MacDonald et al. ( 2015 ) have used the word “regionalism” to characterize the behavior of GIIPS economies (Greece, Ireland, Italy, Portugal, Spain), which have contributed and reacted to the spread of financial stress as a distinctive region. Furthermore, Black et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, MacDonald et al. ( 2015 ) have used the word “regionalism” to characterize the behavior of GIIPS economies (Greece, Ireland, Italy, Portugal, Spain), which have contributed and reacted to the spread of financial stress as a distinctive region. Furthermore, Black et al.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, this result in line with a consolidated literature investigating the role of peripheral countries as determinants of systemic risk in Europe. In particular, MacDonald et al (2015) have used the word "regionalism" to characterize the behavior of GIIPS economies (Greece, Ireland, Italy, Portugal, Spain), which have contributed and reacted to the spread of financial stress as a distinctive region. Furthermore, Black et al (2016) have observed that "the interesting story leading into the sovereign crisis is the Italian and Spanish banks", whose marginal contribution to systemic risk in Europe has grown significantly with the GFC, also in connection with contagion concerns flowing from Greece.…”
Section: Discussionmentioning
confidence: 99%
“…By employing this method, any issues of mis-measurement or with the units of measurement are avoided. In FSIs literature, the variance-equal approach is the most heavily used, given its simplicity and the production of stress indices able to accurately capture market conditions and level of distress (Hakkio and Keeton, 2009, Magkonis and Tsopanakis, 2014, Apostolakis and Papadopoulos, 2014, MacDonald et al, 2015. This means that the equally weighted stress indices successfully represent the prevailing conditions in the financial markets.…”
Section: Measuring Financial Stressmentioning
confidence: 99%
“…We also investigate the relationship between German and Spanish, German and Italian, German and Austrian as well as German and Dutch government bond yields, although we will use a different approach and focus on the corresponding bond yield spreads. Using the government bond yields of Germany as a benchmark is quite common in the literature due to the economic relevance of Germany as the largest EMU economy and its safe haven status (Canarella et al , 2011; Basse, 2014; MacDonald et al , 2015).…”
Section: Literature Overview and History Of The Euro Crisismentioning
confidence: 99%